2010
DOI: 10.1111/j.1468-1331.2010.03263.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cardiovascular risk factors on cognitive function: The Tromsø study

Abstract: Diabetes, smoking, hypertension, and low physical activity were associated with lower cognitive test results. The study suggests that these modifiable risk factors should be emphasized in the prevention of cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 28 publications
4
97
1
4
Order By: Relevance
“…Based on previous studies, HDL-C does not seem to associate with dementia or AD (Li et al 2005;Reitz et al 2010;Arntzen et al 2011) albeit the association is Total cholesterol, HDL cholesterol, systolic blood pressure, body mass index, apolipoprotein A-I, apolipoprotein B, and apolipoprotein B/A ratio were log-transformed before multivariate analysis a Model is not adjusted for total cholesterol apo A-I apolipoprotein A-I, HDL-C high density lipoprotein cholesterol, apo B apolipoprotein B, apo B/A ratio ratio between apo B and apo A-I seen in cross-sectional studies (Merched et al 2000). These findings are in line with our results where death is considered as a competing risk for dementia and AD, and statistically significant association is seen in CIF but not in Cox regression model between HDL-C and AD.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on previous studies, HDL-C does not seem to associate with dementia or AD (Li et al 2005;Reitz et al 2010;Arntzen et al 2011) albeit the association is Total cholesterol, HDL cholesterol, systolic blood pressure, body mass index, apolipoprotein A-I, apolipoprotein B, and apolipoprotein B/A ratio were log-transformed before multivariate analysis a Model is not adjusted for total cholesterol apo A-I apolipoprotein A-I, HDL-C high density lipoprotein cholesterol, apo B apolipoprotein B, apo B/A ratio ratio between apo B and apo A-I seen in cross-sectional studies (Merched et al 2000). These findings are in line with our results where death is considered as a competing risk for dementia and AD, and statistically significant association is seen in CIF but not in Cox regression model between HDL-C and AD.…”
Section: Discussionmentioning
confidence: 96%
“…Higher total serum cholesterol (TC) in midlife is associated with higher risk of AD (Kivipelto et al 2001;Li et al 2005;Solomon et al 2007) but the association of TC and dementia risk is reversed in later life (Mielke et al 2005). Low levels of high density lipoprotein cholesterol (HDL-C) also associate with adverse cerebral white matter changes (Gouw et al 2008;Crisby et al 2010), but no clear association of HDL with the risk of dementia or AD has been found in prospective studies (Li et al 2005;Reitz et al 2005;Reitz et al 2010;Arntzen et al 2011). Apolipoprotein A-I (apo A-I) is the major surface protein of HDL-C, which is associated with lower risk for cardiovascular diseases (CVD).…”
Section: Introductionmentioning
confidence: 99%
“…To date, investigations of smoking and incident MCI specifically, rather than dementia, have been lacking. However, studies examining the impact of current smoking on subsequent change in cognitive performance suggest that current smoking is associated with cognitive decline in individuals without dementia [55,56].…”
Section: Behavioural Factorsmentioning
confidence: 99%
“…Out of nine cross-sectional studies, six studies reported on MI [27,[33][34][35][36][37], three on AP [34,36,37], and five on the CHD compound (MI+AP) [27,[37][38][39][40]. Of the six studies investigating MI, four found a significant relation with poor cognitive functioning [27,33,34,37], and two studies found no association with prevalent cognitive impairment [35,36].…”
Section: Case-control Studiesmentioning
confidence: 99%
“…In the meta-analysis, four studies representing 623,588 persons could be included [35,36,38,39]. CHD was not significantly associated with an increased risk of cognitive impairment or dementia (OR = 1.23, 95%CI = 0.76-1.97, p = 0.398; Figure H in S5 Appendix).…”
Section: Case-control Studiesmentioning
confidence: 99%